Read Gmail on you desktop via POP3 or IMAP. - Spanbauer, Scott
A guide on alternative access to Gmail account through the use of POP3 and IMAP via email programs such as Outlook, Outlook Express, Thunderbird or Apple Mail.
Keywords: Email ? Acess